Dystocia Due to Fetal Ascites in a Buffalo (Bubalus bubalis) - Khatti, Amit; Saini, Gitesh; Aamir Nehru, Dawoud; Bhardwaz , Anavil (The Indian Journal of Animal Reproduction, 2025)
An eight-year, fifth parity buffalo was reported to Veterinary Clinical Complex, College of Veterinary Science, Rampura  Phul with problem of obstructed fetus in birth canal, hyperthermia and severe distress. The case was diagnosed as  dystocia due fetal ascites and complicated by hyperthermia. Successful management of hyperthermia and per-vaginal  delivery through obstetrical maneuver is presented in this paper.
Keywords: Ascites; Buffalo; Dystocia; Hyperthermia